2020
DOI: 10.1159/000513093
|View full text |Cite
|
Sign up to set email alerts
|

Association of Chemokine (C-C Motif) Receptor 5 and Ligand 5 with Recovery from Major Depressive Disorder and Related Neurocognitive Impairment

Abstract: <b><i>Introduction:</i></b> Inflammatory processes play an important role in the pathophysiology of major depressive disorder (MDD), but their relevance for specific symptoms such as neurocognitive impairment is rarely investigated. <b><i>Methods:</i></b> In this observational study, we investigated the changes of leukocyte chemokine (C-C motif) receptor 5 (CCR5) and ligand 5 (CCL5) mRNA levels and inflammatory cytokines in 60 MDD patients before (PRE) and after … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
(58 reference statements)
0
3
1
Order By: Relevance
“…These correlations between IL-1β, IFN-γ, and IL-9 explain the negative association of IFN-γ and IL-1β with subjective cognitive function and the positive association of IL-9 with subjective cognitive function in this study. Furthermore, IL-1β interacts with RANTES and registers an important role in brain pathology (Marques et al, 2013), but a previous study found no correlation between RANTES and objective cognitive function (Bauer et al, 2020). In this study, a positive correlation was observed between RANTES and subjective cognitive function, and the mechanism of this correlation needs further investigation.…”
Section: Discussioncontrasting
confidence: 49%
“…These correlations between IL-1β, IFN-γ, and IL-9 explain the negative association of IFN-γ and IL-1β with subjective cognitive function and the positive association of IL-9 with subjective cognitive function in this study. Furthermore, IL-1β interacts with RANTES and registers an important role in brain pathology (Marques et al, 2013), but a previous study found no correlation between RANTES and objective cognitive function (Bauer et al, 2020). In this study, a positive correlation was observed between RANTES and subjective cognitive function, and the mechanism of this correlation needs further investigation.…”
Section: Discussioncontrasting
confidence: 49%
“…Within the CNS it affects microglial chemotaxis and HPA axis modulation ( Singhal and Baune, 2018 ). An observational study in 60 MDD patients who underwent 5 weeks of antidepressant treatment reported that, relative to non-responders, RANTES/CCL5 and CCR levels were significantly lower in responders, even prior to treatment ( Bauer et al, 2020 ). In our study, the partial interaction for RANTES/CCL5 did not survive correction for FDR in the change association models ( B = 0.514, p = 0.021, q = 0.103).…”
Section: Discussionmentioning
confidence: 99%
“…These correlations between IL-1β, IFN-γ, and IL-9 explain the negative association of IFN-γ and IL-1β with subjective cognitive function and the positive association of IL-9 with subjective cognitive function in this study. Furthermore, IL-1β interacts with RANTES and registers an important role in brain pathology [ 43 ], but a previous study found no correlation between RANTES and objective cognitive function [ 44 ]. In this study, a positive correlation was observed between RANTES and subjective cognitive function, and the mechanism of this correlation needs further investigation.…”
Section: Discussionmentioning
confidence: 99%